A Special Font for People with Dyslexia: Does it Work and, if so, why?. (19th May 2016) - Marinus, Eva; Mostard, Michelle; Segers, Eliane; Schubert, Teresa M.; Madelaine, Alison; Wheldall, Kevin
Abstract : In 2008 Christian Boer, a Dutch artist, developed a special font ("Dyslexie") to facilitate reading in children and adults with dyslexia. The font has received a lot of media attention worldwide (e.g., TheGuardian.com, Slate.com, TheAtlantic.com, USA Today, and io9.com). Interestingly, there is barely any empirical evidence for the efficacy of Dyslexie. This study aims to examine if Dyslexie is indeed more effective than a commonly used sans serif font (Arial) and, if so, whether this can be explained by its relatively large spacing settings. Participants were 39 low‐progress readers who were learning to read in English. They were asked to read four different texts in four different font conditions that were all matched on letter display size (i.e., x‐height), but differed in the degree to which they were matched for spacing settings. Results showed that low‐progress readers performed better (i.e., read 7% more words per minute) in Dyslexie font than in standardly spaced Arial font. However, when within‐word spacing and between‐word spacing of Arial font was matched to that of Dyslexie font, the difference in reading speed was no longer significant. We concluded that the efficacy of Dyslexie font is not because of its specially designed letter shapes, but because of its particular spacing settings. Copyright © 2016 John Wiley & Sons, Ltd.